Tunisia's Success in Consolidating Its Democracy One Decade Post-the Arab Spring - Ahmad Sahide; Yoyo Yoyo; Ali Muhammad (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
The political turmoil in Tunisia at the end of 2010 opened the door to the democratization of Arab countries. This event, widely known as The Arab Spring, presented a dream for the Arab community to live a better life under a democratic system. However, after a decade of progress, only Tunisia has succeeded in consolidating its democracy among the Arab countries that have been affected by the political turmoil. This paper tries to read the success factors for Tunisia in consolidating its democracy by using the theory of democracy from Robert Dahl, Jack Snyder, and Georg Sorensen. This study concludes that democracy in Tunisia is already included in the category of matured democracy according to Snyder's theory or has entered the category in which a democratic culture has begun to develop (Sorensen) and fulfills the elements of a democratic state according to Dahl. This success is inseparable from internal and external factors. The internal factor is the foundation of a civil society built before The Arab Spring and the openness of viewpoints of political actors after the political upheaval. Meanwhile, the external factor is the absence of America as the dominant actor in Tunisia because Tunisia is considered a ferry country. Tunisia also proves that Islam and democracy can go hand in hand, and this is a refutation of the pessimistic views of the scholars on Islam and democracy that can go hand in hand.